Control of Intestinal Inflammation, Colitis-Associated Tumorigenesis, and Macrophage Polarization by Fibrinogen-Like Protein 2 - Zhu, Ying; Zhou, Jie; Feng, Yi; Chen, Liying; Zhang, Longhui; Yang, Fei; Zha, Haoran; Wang, Xinxin; Han, Xiao; Shu, Chi; Wan, Yisong Y.; Li, Qi-Jing; et al. (Frontiers in Immunology, 2018)
Fibrinogen-like protein 2 (Fgl2) is critical for immune regulation in the inflammatory state. Elevated Fgl2 levels are observed in patients with inflammatory bowel disease (IBD), but little is known about its functional significance. In this study, we sought to investigate the role of Fgl2 in the development of intestinal inflammation and colitis-associated colorectal cancer (CAC). Here, we report that Fgl2 deficiency increased susceptibility to dextran sodium sulfate (DSS)-induced colitis and CAC in a mouse model. During colitis development, the expression of the membrane-bound and secreted forms of Fgl2 (mFgl2 and sFgl2, respectively) in the colon were increased and predominantly expressed by colonic macrophages. In addition, using bone marrow chimeric mice, we determined that Fgl2 function in colitis is strictly related to its expression in the hematopoietic cells. Loss of Fgl2 induced the polarization of M1, but suppressed that of M2 both in vivo and in vitro, independent of intestinal inflammation. Thus, Fgl2 suppresses intestinal inflammation and CAC development through its role in macrophage polarization, and may serve as a therapeutic target in inflammatory diseases, including IBD.